Performance analysis of repeater spoofing suppression based on GNSS multi-beam receiver - Ren, Binbin; Chen, Feiqiang; Ni, Shaojie; Han, Chunyang; Lu, Zukun; Han, Shujian (Frontiers in Physics, 2022)
In order to analyze the anti-spoofing performance of the Global Navigation Satellite System (GNSS) multi-beam anti-jamming receiver in the presence of direct repeater spoofing, this paper deduces the theoretical formulas of the output real signal and the direct repeater spoofing signal power of the multi-beam anti-jamming receiver using the minimum variance distortionless response (MVDR) algorithm, when the number of snapshots is limited. The influence of the power of the spoofing signal reaching the surface of the antenna array on the output power of the real signal and the spoofing signal is analyzed in detail. The analysis shows that no matter how the power of the direct repeater spoofing signal is set, the multi-beam anti-jamming receiver using the MVDR algorithm can always suppress the spoofing below the real signal power level, and the suppression effect is more significant when the spoofing signal-to-noise ratio is high. Finally, the correctness of the conclusion is verified by simulation.